فقه الأقليات في ضوء مقاصد الشريعة : ولاية كيرلا بالهند أنموذجًا - لاكل، عبد الواسع (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study examines the issues of Muslim minority in India, in Kerala particularly. It looks at their struggle in sustaining the survival of their cultural and religious traditions as set out by Fiqh al-Aqaliyyah. The study looks at the complex challenges, theoretically and historically, faced by the Muslims of Kerala in meeting the objectives of the Shari'a. The state of Kerala is located in the far south of India, characterized by peaceful coexistence and religious tolerance as the rules and regulations followed by the Muslims of India in other states may not be suit the Muslims of Kerala; their circumstances are different from each other. These states have been known for the religious clashes and sectarian conflicts, while the Kerala people are known to share their views with each other in religious, social and political events without regard to what each sect adopts in its beliefs or doctrine. The research follows the inductive method. The researcher collects the scientific material related to the chosen subject, analyzes it to extract the benefits from it, and expresses his opinions on some issues of the Muslim minority in Kerala with reference to the backgrounds and the circumstances behind them. The issues faced by the Muslim minority in Kerala may appear to be easy and simple, but they have another aspect that affects the relationship of Muslims with others. The research concluded that the Muslim minorities in Kerala are in need of a new jurisprudence in the light of Maqasid al-Sharia and it should be characterized itself with co-existence in order to serve as a bridge between Islam and others.